Friend or Foe? Re-visioning Friendships Beyond Borders - Ali, Zaynab (Pivot: A Journal of Interdisciplinary Studies and Thought, 2022)
Destruction is transnational: homes, places of worship, healing and community are annihilated and the landscapes of counties are altered. Meanwhile, civilians are left to grapple with their new realities. However, the attention afforded to these disasters varies depending on factors of race, ethnicity, creed, and nationality—the ties that are held dear are the very bonds that determine friends from foes. In most cases, however, news of violence is met by indifference. Individuals are unable to empathize with strangers whose lives are being shattered. This paper analyzes Atiq Rahimi’s Earth and Ashes (1999/tr.2002) in order to argue that the vehicle transporting one away from apathy is a re-visioning of friendship. Questions of focus include, how is empathy formed for those who are long-gone, or for those whose faces one cannot see? And how can friendship help bridge this gap? An ethical turn to analyzing friendships that can forge connections around the world requires a “re-visioning” of what it means to be a witness to another’s distress as outlined by Oliver Kelly in Witnessing: Beyond Recognition and Michel Foucault’s “Friendship as a way of Life.” In Earth and Ashes transit and re-visioning operate on two levels: physically across an unforgiving landscape to the coal mines, and emotionally through death and destruction to the eventual acceptance of infinite loss. This paper argues that progress down the road and past the checkpoint is enabled by fleeting relations working as vehicles: Dastaguir befriends a shopkeeper, a fellow bus passenger, and a servant who help facilitate his passage through the hazardous landscapes of war and trauma. As witnesses to Dastaguir’s transit, these friends help catalyse, and cauterise, exile from family, community, safety—from life itself until an ethical re-visioning of friendships beyond borders can occur.